A combined strategy for screening a clustered mobile population returning from highly endemic areas for Plasmodium falciparum - Li, Mei; Li, Jun; Xia, Zhigui; Xiao, Ning; Jiang, Weikang; Wen, Yongkang (The Journal of Infection in Developing Countries, 2017)
Introduction: Early and accurate diagnosis of imported malaria cases in clusters is crucial for protecting the health of patients and local populations, especially confirmed parasitic persons who are asymptomatic. Methodology: A total of 226 gold miners who had stayed in highly endemic areas of Ghana for more than six months and returned in clusters were selected randomly. Blood samples from them were tested with microscopy, nest polymerase chain reaction, and rapid diagnostic test (RDT). The sensitivity, specificity, predictive values, agreement rate, and Youden’s index of each of three diagnostic methods were calculated and compared with the defined gold standard. A quick and efficient way to respond to screening such a clustered mobile population was predicted and analyzed by evaluating two assumed results of combining microscopy and RDT with or without symptoms of illness. Results: The rate of the carriers of malaria parasites in the populations of gold miners was 19.47%, including 39 P. falciparum. Among the three diagnostic methods, the microscopy method showed the highest specificity, while the RDT method showed the highest sensitivity but the lowest specificity in detecting P. falciparum. The assumed results of combining RDT and microscopy with symptoms showed the best results among all the test results in screening P. falciparum. Conclusions: It was too complex and difficult to catch all parasite carriers in a short period of time among populations with such a complicated situation as that in Shanglin County. A strategy of combing microscopy and RDT for diagnosis is highly recommended.